(untitled) (International Journal of Engineering and Computer Science, 2023)
Transaction volumes throughout the world are growing very fastly and that result in the complexities, vulnerabilities, inefficiencies, and higher costs of current transaction systems. The growth of ecommerce, online banking, and in-app purchases, is increasing and is more popular among the people around the world. And transaction volumes are increasing with the advent of the Internet of Things (IoT). Objects, such as laptop, washing machines and groceries are running low and cars that deliver themselves to your door. To meet these challenges and others we need faster payment methods that are trustworthy and require no specialized equipment with no chargebacks or monthly fees and offer a good bookkeeping solution for ensuring transparency.